Identification of genes associated with endometrial cell ageing. (1st December 2020) - Kawamura, Teruhiko; Tomari, Hiroyuki; Onoyama, Ichiro; Araki, Hiromitsu; Yasunaga, Masafumi; Lin, Cui; Kawamura, Keiko; Yokota, Natsuko; Yoshida, Sachiko; Yagi, Hiroshi; Asanoma, Kazuo; Sonoda, Kenzo; et al.
Abstract: Ageing of the uterine endometrium is a critical factor that affects reproductive success, but the mechanisms associated with uterine ageing are unclear. In this study, we conducted a qualitative examination of age-related changes in endometrial tissues and identified candidate genes as markers for uterine ageing. Gene expression patterns were assessed by two RNA-sequencing experiments using uterine tissues from wild type (WT) C57BL/6 mice. Gene expression data obtained by RNA-sequencing were validated by real-time PCR. Genes expressing the pro-inflammatory cytokines Il17rb and chemokines Cxcl12 and Cxcl14 showed differential expression between aged WT mice and a group of mice composed of 5- and 8-week-old WT (young) animals. Protein expression levels of the above-mentioned genes and of IL8, which functions downstream of IL17RB, were analysed by quantitative immunohistochemistry of unaffected human endometrium tissue samples from patients in their 20s and 40s (10 cases each). In the secretory phase samples, 3, 3ʹ- diaminobenzidine staining intensities of IL17RB, CXCL12 and CXCL14 for patients in their 40s were significantly higher than that for patients in their 20s, as detected by a Mann–hitney U test. These results suggest that these genes are candidate markers for endometrial ageing and for prediction of age-related infertility, although confirmation of these findings is needed in larger studies involving fertile and infertile women.